The trend towards using electronic human resources management and its role in the effectiveness of the offices of inspectors general - طه عبد الرحمن مصطفى; حسن نادية ناجي (Journal of Economics and Administrative Sciences, 2015)
This research aims to study the trend towards using electronic human resource management and its role in the effectiveness of the Offices of Inspectors General. The dimensions of the trend towards using electronic human resource management are: (ease of use, system quality, system suitability, and practical benefit). The dimensions of organizational effectiveness are: (flexibility, resource access, clarity of objectives, qualified human resources, and cohesive human resources). The research used a questionnaire as the primary data collection tool, in addition to personal interviews with some employees of the Offices of Inspectors General. The research sample consisted of four offices, representing 10% of the total number of Offices of Inspectors General in Iraqi ministries: the Office of the Inspector General of the Ministry of Communications, the Office of the Inspector General of the Ministry of Oil, the Office of the Inspector General of the Ministry of Higher Education and Scientific Research, and the Office of the Inspector General of the Ministry of Industry and Minerals. Therefore, the research hypothesized that the trend towards using electronic human resource management is related to the effectiveness of the Offices of Inspectors General, and that this trend influences their effectiveness. A sample of (107) individuals was selected, comprising department and division managers in the research offices. A range of statistical methods were used, and the research reached several conclusions, including the benefits gained by offices from implementing electronic human resources management. These benefits included better control over work procedures, a reduction in the time employees needed to complete their tasks correctly, and the ability to perform other duties. All of this contributes to enhancing office efficiency. Finally, the research recommended several measures, most importantly the need to review the experiences of Arab countries that have implemented electronic human resources management in their organizations and achieved positive results, thereby impacting the effectiveness of their human resources and organizational efficiency. It also recommended adapting these practices to the specific nature of office work.